ID: 187. Issue 1 (November 2015) - Graf, Laura; Sendker, Franziska; Dick, Alexej; Barth, Emanuel; Marz, Manja; Daumke, Oliver; Kochs, Georg
<x xml:space="preserve">Abstract</x> Human myxovirus resistance protein A (MxA) is an interferon-induced GTPase and part of the host cell defense against influenza viruses. It has a three-domain architecture with an amino-terminal GTPase (G) domain and a carboxy-terminal stalk responsible for oligomerization and viral target recognition. The MX1 gene, encoding MxA, is highly conserved and only a few single nucleotide polymorphisms are described in the human population. In this study we investigate whether and how allelic variations in MxA influence its antiviral function. Two rare nucleotide changes identified in the MX1 gene of healthy individuals result in amino acid exchanges at positions 255 and 268 in the G domain. GTPase and Minireplicon assays revealed that the V268M exchange showed some reduction in GTP hydrolysis, but only a slightly reduced antiviral activity against influenza A virus. However, the G255E exchange caused a complete loss of GTPase and antiviral activity of MxA. Further biochemical analyses of this naturally occurring mutation revealed the central role of GTP binding and hydrolysis for the antiviral mechanism of MxA. Using bioinformatics tools we are currently identifying additional allelic variations in MxA. Their characterization will answer the question how polymorphisms in the MX1 gene influence the antiviral capacity of MxA and whether these are enriched in patients suffering from severe influenza as has been described recently for IFITM3, another interferon-induced antiviral restriction factor.